The effects of playing tactics on creating scoring opportunities in random matches from US Major League Soccer - Gonzalez-Rodenas, J.; Lopez-Bondia, I.; Calabuig, F.; Perez-Turpin, J. A.; Aranda, R. (International Journal of Performance Analysis in Sport, 2015)
The aim of this study was to examine the effects of playing tactics on the creation of scoring opportunities in random matches from US Major League Soccer 2014, taking into account both contextual and defensive variables. The sample included 3253 team possessions corresponding to 30 randomly selected matches. Multidimensional qualitative data from 10 categorical variables was analysed by means of descriptive analysis and multiple logistic regression analysis. Contextual variables such as match location (p=0.049), match half (p=0.043) and match status (P=0.032) were associated with creating scoring opportunities. With regards playing tactics, set plays created a higher proportion of scoring opportunities (28.1±13.7%) than recoveries (11.2±5.2%) and restarts (8.1±5.2%)